2021
DOI: 10.1002/ls.1567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon nano onions on the tribological performance of food‐grade calcium sulfonate complex grease

Abstract: To improve the lubricity of the as‐prepared food‐grade calcium‐based grease, the effects of nano‐additive carbon nano onions (CNOs) on the tribological properties are systematically investigated using a ball‐disc wear tester. The properties of CNOs‐containing food‐grade calcium sulfonate complex greases (CSCG‐FG) were characterised by thermogravimetric analyser, rheometer and electrochemical workstation, Listeria monocytogenes, X‐ray photoelectron spectrometer and Raman spectrometer. The results revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Nano-onion-like fullerene, a member of the zero-dimensional fullerene family, is commonly referred to as onion-like carbon (OLC), which exhibits near-spherical structures composed of multiple layers of closed fullerene carbon shells . Due to its unique structural characteristics, OLC possesses a high specific surface area and mechanical strength, both of which are conducive to its lubricating effect. He et al prepared high-purity and high-reproducibility OLC via a one-step gas-phase explosion method, which improves the lubricating ability of 150SN mineral oil as a lubricant additive . Wang et al incorporated OLC as an additive into calcium sulfonate complex grease and found that the lubricating performance of the grease improved significantly with 0.10 wt % addition, reducing the average COF and wear volume by 31.4 and 70.0%, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nano-onion-like fullerene, a member of the zero-dimensional fullerene family, is commonly referred to as onion-like carbon (OLC), which exhibits near-spherical structures composed of multiple layers of closed fullerene carbon shells . Due to its unique structural characteristics, OLC possesses a high specific surface area and mechanical strength, both of which are conducive to its lubricating effect. He et al prepared high-purity and high-reproducibility OLC via a one-step gas-phase explosion method, which improves the lubricating ability of 150SN mineral oil as a lubricant additive . Wang et al incorporated OLC as an additive into calcium sulfonate complex grease and found that the lubricating performance of the grease improved significantly with 0.10 wt % addition, reducing the average COF and wear volume by 31.4 and 70.0%, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…14 Wang et al incorporated OLC as an additive into calcium sulfonate complex grease and found that the lubricating performance of the grease improved significantly with 0.10 wt % addition, reducing the average COF and wear volume by 31.4 and 70.0%, respectively. 15 The OLC usually ranges in size from 2 to 220 nm, and various preparation methods are employed, including arc discharge, 18 hydrothermal synthesis, 19 vacuum heat treatment, 20 combustion. 21 Especially, the preparation of OLC by collecting candle ash from burned candles has the salient features of simplicity and cost effectiveness, making it widely used.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation